2016
DOI: 10.1186/s12913-016-1589-x
|View full text |Cite
|
Sign up to set email alerts
|

The success of the Uttarakhand Cluster: a case study of organisational change towards disability inclusive development

Abstract: BackgroundPersons with disability are often marginalised and excluded from international development efforts. This case study reviews the success of Uttarakhand Cluster of development NGOs in changing organisational behaviour towards being disability inclusive in their development (DID) activities.MethodsA triangulation of qualitative research methods was used, including key informant interviews, focus group discussions and review of textual data.ResultsThe results synthesise data into Kotter’s framework for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Network approaches between OPDs have also been described in other literature (Armstrong, 1993;Cobley, 2013;Deepak et al, 2013;Hemingway & Priestley, 2006;Kleintjes et al, 2013;Miles et al, 2012). The value of the Uttarakhand Cluster as a network has been reviewed in previous studies (Grills et al, 2012;Grills et al, 2016). The realist evaluation described this process of visiting other OPDs as being useful in terms of modelling group function, increasing enthusiasm, sharing knowledge, and increasing confidence, which in turn led to earlier group formation, more rapid transfer of responsibility from the NGO to the OPD members, and increased participation in society.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Network approaches between OPDs have also been described in other literature (Armstrong, 1993;Cobley, 2013;Deepak et al, 2013;Hemingway & Priestley, 2006;Kleintjes et al, 2013;Miles et al, 2012). The value of the Uttarakhand Cluster as a network has been reviewed in previous studies (Grills et al, 2012;Grills et al, 2016). The realist evaluation described this process of visiting other OPDs as being useful in terms of modelling group function, increasing enthusiasm, sharing knowledge, and increasing confidence, which in turn led to earlier group formation, more rapid transfer of responsibility from the NGO to the OPD members, and increased participation in society.…”
Section: Discussionmentioning
confidence: 96%
“…In 2009, the Cluster identified that persons with disabilities were often excluded from health and development programmes. In response, the Cluster decided to focus on disability, both in terms of awareness-raising and the promotion of disability inclusive development (Grills et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Burans implemented Nae Umeed in conjunction with CHGN-UKC, a partnership of community health and development non-governmental organisations (NGOs) that collaborate on training, resource development, advocacy, and research partnerships (Grills et al, 2016; Uttarakhand Community Health Cluster, 2022). The implementation strategy aimed to engage and support CHGN-UKC partners to deliver Nae Umeed within their existing work areas.…”
Section: Methodsmentioning
confidence: 99%
“…Poverty is associated with marginalised people in development (Grills et al, 2016). It means that the poor are not accommodated in the development process In the future, this condition is expected to change through 9 (nine) priority agenda of the Indonesian president called Nawacita.…”
Section: Discussionmentioning
confidence: 99%
“…Many groups of people become marginalised in development just because of their gender, ethnic groups, age, sexual orientation, physical disabilities, and poverty. Nevertheless, they also have the same right to participate in development (Grills et al, 2016). Therefore, issues of the need for inclusive development today arise.…”
Section: Introductionmentioning
confidence: 99%